Controllable Schottky barriers and contact types of BN intercalation layers in graphene/MoSi2As4 vdW heterostructures via applying an external electrical field. Issue 30 (26th July 2022) - Guo, Yuan; Dong, Yujing; Cai, Xiaolin; Liu, Liangliang; Jia, Yu
Abstract : The graphene/MoSi2 As4 vdW heterostructure with high carrier mobility and strong optical absorption intensity can be applied to high-speed FET. Moreover, the opening band gap can be achieved in the graphene/BN/MoSi2 As4 heterostructure. Abstract : Graphene-based van der Waals (vdW) heterostructures have opened unprecedented opportunities for various device applications due to their rich functionalities and novel physical properties. Motivated by the successful synthesis of a MoSi2 N4 monolayer ( Science, 2020, 369, 670), in this work by means of first-principles calculations we construct and investigate the interfacial electronic properties of the graphene/MoSi2 As4 vdW heterostructure, which is expected to be energetically favorable and stable. Our results show that the graphene/MoSi2 As4 heterostructure forms an n-type Schottky contact with a low barrier of 0.12 eV, which is sensitive to the external electric field and the transformation from an n-type Schottky contact to a p-type one can be achieved at 0.2 V Å −1 . The small effective masses and strong optical absorption intensity indicate that the graphene/MoSi2 As4 heterostructure will have a high carrier mobility and can be applied to high-speed FET. Importantly, we also show that the opening band gap can be achieved in the graphene/BN/MoSi2 As4 heterostructure and the type-I band alignment can transform into type-II under an external electric field of −0.2 V Å −1 . These findings demonstrate that the graphene/MoSi2 As4 heterostructure can be considered as a promising candidate for high-efficiency Schottky nanodevices.